Systematic Understanding of Pathophysiological Mechanisms of Oxidative Stress-Related Conditions—Diabetes Mellitus, Cardiovascular Diseases, and Ischemia–Reperfusion Injury - Wang, Mengxue; Liu, Yun; Liang, Yin; Naruse, Keiji; Takahashi, Ken (Frontiers in Cardiovascular Medicine, 2021)
Reactive oxygen species (ROS) plays a role in intracellular signal transduction under physiological conditions while also playing an essential role in diseases such as hypertension, ischemic heart disease, and diabetes, as well as in the process of aging. The influence of ROS has some influence on the frequent occurrence of cardiovascular diseases (CVD) in diabetic patients. In this review, we considered the pathophysiological relationship between diabetes and CVD from the perspective of ROS. In addition, considering organ damage due to ROS elevation during ischemia–reperfusion, we discussed heart and lung injuries. Furthermore, we have focused on the transient receptor potential (TRP) channels and L-type calcium channels as molecular targets for ROS in ROS-induced tissue damages and have discussed about the pathophysiological mechanism of the injury.